Helicobacter pylori en heces y su incidencia en patologías gástricas en adultos de 20 a 60 años cooperativa simón Bolívar cantón Babahoyo Los Ríos primer semestre 2015 - Espin Jara, Madelein Katiusca (2015)
Half the world's population is infected with Helicobacter pylori. People living in developing countries or in overcrowded or unsanitary conditions are most likely to contract the bacterium, which is transmitted from one person to another. That is why in the present study aimed to determine the incidence of Helicobacter pylori in gastric diseases in adults 20-60 years of Simon Bolivar Canton Cooperative Los Rios Province Babahoyo during the first half of 2015. The methods used in the development of this research study were inductive methods - deductive and analytical. The type of study that was conducted at the Laboratory research, because by himself he could determine the incidence of Helicobacter pylori in the cooperative inhabitants Simon Bolivar. They investigated 94 adults of 20-60 years of Simon Bolivar Cooperative of which 38.3% are males and 61.7% females. Once the tests were positive HpsAg made 69.1% of the study population and 30.9% were negative, where 40.0% were male and 60.0% were female. By linking Helicobacter Pylori with the sex variable value is the dominant female with 58.3%; with age of 20-30 years 36.9%. 44.7% of adults are high school graduates, where 38.1% are male and 61.8% are women. 58.5% of adults do not wash their hands before eating and after using the bathroom, 61.7% do not wash fruit before eating, 38.3% consume alcoholic beverages, 31.9% had the habit of smoking, 76.6 % of adults have no knowledge about the disease. Upon receipt of the samples the adults had symptoms of which 41.5% had heartburn, 34.0% had an upset stomach, 24.5% had wanted to vomit. When performing the survey questions it was learned that 60.6% of adults have not conducted the review of Helicobacter Pylori and that 33.0% have been diagnosed with this disease. 80.9% deposition of feces made in the latrine, 59.6% get water through the pipes for household consumption and 59.6% consume water without treatment